2003
DOI: 10.1002/jbm.b.10066
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of interconnected highly porous polymeric structures by a replication and freeze‐drying process

Abstract: Three-dimensional degradable porous polymeric structures with high porosities (93-98%) and well-interconnected pore networks have been prepared by freeze-drying polymer solutions in the presence of a leachable template followed by leaching of the template. Templates of the pore network were prepared by fusing sugar or salt particles to form a well-connected structure. The interstices of the template were then filled with a polymer solution (5-15% w/v) in 1,4-dioxane, followed by freeze-drying of the solvent. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 35 publications
(30 reference statements)
1
72
0
Order By: Relevance
“…Evident differences between AS and GS surfaces of obtained polymer and composite membranes were found. AS surfaces of materials prepared by TIPS method exhibited open, irregular, cellular microporous structure, a typical morphology formed by solid-liquid phase separation [12][13][14]. Pore size decreased, and their shape become more regular upon addition of BG particles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evident differences between AS and GS surfaces of obtained polymer and composite membranes were found. AS surfaces of materials prepared by TIPS method exhibited open, irregular, cellular microporous structure, a typical morphology formed by solid-liquid phase separation [12][13][14]. Pore size decreased, and their shape become more regular upon addition of BG particles.…”
Section: Resultsmentioning
confidence: 99%
“…Phase separation methods, predominantly the nonsolvent-induced phase separation (NIPS, also called as immersion-precipitation) [3,10,11] and the thermalinduced phase separation (TIPS) [10,[12][13][14][15] techniques have been used to obtain porous polymer, as well as polymer-ceramic composite scaffolds and membranes for TE applications. The obtained material morphology, as well as the corresponding pore size and shape may vary widely depending on the manufacturing process conditions; from dense to highly porous, and with pores size from submicron scale to tens of microns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Hou et al [25] fabricated high porosity PDLLA foams and found the compressive moduli of scaffolds of 97.2% and 97.7% porosity to be 0.30 MPa and 0.23 MPa, respectively. In another study, Hou et al [26] related compressive moduli to the porosities of the scaffolds according to the power law relationship (Eq.…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…Different porogens are used frequently for the leaching techniques. These are, for example, NaCl [258], as perhaps the most common leaching substance, as well as paraffin spheres [170,259,260], sugar crystals [261][262][263] or gelatin [264], which serve as place holders for pores and their interconnections in the actual scaffold formation process. These spacers are removed by leaching following the main processing step.…”
Section: Leaching Techniquementioning
confidence: 99%